(De)Scribing home in apartheid South Africa: Locating Sepedi literature in the discourse. Issue 1 (2nd January 2021) - Mokgoatšana, Sekgothe
Abstract : The article joins the ongoing discourse of subalterns and the manner in which they inscribe their lives as scripts to explain their relationship with spaces and places they consider to be home. It also contributes from the same subaltern position to the heated debate in settler/colonial studies which are part of the grand theory of postcolonial discourse. The subaltern, as I shall illustrate is not always the muted, waiting-to-be-rescued subject, but a revolutionary self, resisting displacement, erasure and deracination. I will show how NS Puleng writing in Sepedi unsettles the master narrative discourses of dominance, thus giving voice to the voiceless. I shall further demonstrate how the writer defines and constructs 'home' despite the borders set by colonial/apartheid machinations. To bring home this debate, I will largely focus on NS Puleng's two classical poetic works, namely Malopo a boreti and Seipone sa madimabe to reflect how 'home' is constructed in Sepedi literature. The author has purposively selected seven poems as units of analysis, namely Ga ke mofaladi, Ke kae mo, Gareadulelaruri, Gona kua matopeng, and Matlakašuthe from Malopo a boreti, and two from Seipone sa madimabe: Bohwa bja ka and Mo ke bokhutšo .